Efficacy of nutritional support in combination with standard Buruli ulcer treatment: A case study in Côte d’Ivoire - Yao Didier Koffi; Paul Aboa Koffi; Evans Ehouman; Saint-Pierre Kouadio; Mamadou Kaloga (Journal of Clinical Tuberculosis and Other Mycobacterial Diseases)
Background: Buruli ulcer (BU) is an infectious skin disease caused by Mycobacterium ulcerans. It primarily affects disadvantaged rural populations and mainly impacts children who are chronically malnourished being especially vulnerable. In Côte d’Ivoire, the estimated prevalence of BU in children is 30 %. Malnutrition may further deteriorate the nutritional status of these individuals. This study aimed to compare the healing time of BU patients treated with the standard protocol (SP) of 8 weeks of rifampicin and clarithromycin combined with wound care versus those treated with the standard protocol plus nutritional support using Skin Renewal Medicine-1 (SPSRM-1) (UNHWA Medical Centre, Seoul, Republic of Korea). Additionally, the study measured the effects of SRM-1 on the patients’ nutritional status. Method: This was a prospective, randomized, single-blind paired interventional study conducted in BU-endemic health districts of Côte d’Ivoire. This 12-month study had two arms: the standard protocol versus the test treatment (SPSRM-1). SRM-1 is a cereal-based nutraceutical composed of 60 % cereal, 25 % vegetable, and 15 % plant concentrate. Patients included in the study had uncomplicated category I and II ulcerations without comorbidities. Nutritional status including haemoglobin, albumin levels, and body mass index (BMI) was evaluated from enrolment to the end of the study, alongside ulcer healing rates. Results: Sixty BU wound patients were enrolled: 30 in the control group and 30 in the test group, with a mean age of 22 years. Of the patients, 28.3 % were malnourished, and 42 % had hypoalbuminemia. At the primary endpoint, 6 patients (20.0 %) in the SPSRM1 and 5 patients (16.7 %) in the SP group achieved complete epithelialization, with a reduction rate of 0.7 % per day in the SPSRM1 group compared to 0.3 % per day in the SP group. Patients who received SRM-1 had a higher BMI than those who did not, with a mean difference of 1.72 kg/m2 favouring the test group. Haemoglobin and albumin levels also showed improvement at the secondary endpoint compared to the control group. Conclusion: This study demonstrated the potential benefit of adding nutritional support to improve BU treatment outcomes, by shortening the healing time of ulcerations. However, further studies with larger sample sizes are necessary to confirm these findings.